Multi-objective vessel routing problems with safety considerations: A review - Nazanin Sharif; Mikael Rönnqvist; Jean-François Cordeau; Jean-François Audy; Gurjeet Warya; Trung Ngo (Maritime Transport Research)
This paper provides a review of vessel route planning with a focus on safety considerations and the complexity of multi-objective decision-making processes. This complexity arises from the difficulty of finding an appropriate balance between several objectives and safety concerns, often conflicting, that adequately reflects the preferences of the decision makers. The maritime industry faces the challenge of enhancing vessel route optimization for safety, operational efficiency, and cost-effectiveness. We thus describe quantitative methods to find routes that effectively balance multiple objectives, including safety, fuel consumption, and route duration. A significant focus is on the complexity of multi-criteria decision making in this area, highlighting various methodologies for balancing the different objectives. Safety is critical in this context, involving a thorough consideration of navigational risks, environmental factors, and compliance with International Maritime Organization regulations. Specifically, we introduce quantitative approaches for integrating key safety aspects into the decision-making process, including dynamic stability, the probability of bow slamming, and the occurrence of green water.